PHLEBOTOMINAE (DIPTERA: PSYCHODIDAE) EM DUAS CIDADES COM TRANSMISSÃO INTENSA DE LEISHMANIOSE VISCERAL, BRASIL - Aline Márcia dos Santos Villasanti (2022)
The studies of the sandflies fauna make it possible to assess the presence of vectors and provide subsidies for surveillance and control measures for leishmaniasis. The objective of this study is to describe the sandflies fauna in Campo Grande (MS) and São Luís (MA), as well as the sociodemographic and environmental indices of urban areas. Specimens were collected monthly, for three consecutive nights, with CDC-type light traps at 20 points in each city. The traps were installed at 6pm and removed at 6am. Sociodemographic information was obtained from the database of the Brazilian Institute of Geography and Statistics (IBGE) and environmental data (rainfall, relative humidity, temperature and wind speed) from the National Institute of Meteorology (INMET). In Campo Grande, the captures took place from July 2021 to June 2022, while in São Luís the collections were conducted from August 2021 to March 2022. In both cities, 8,198 sandflies were collected. Of the total, 5,849 come from Campo Grande and 2,349 from São Luís. We captured 5,670 (69.16%) males and 2,528 (30.84%) females. Lutzomyia longipalpis was the most frequent species in Campo Grande (MS) with 5,823 (99.55%) and São Luís (MA) with 2,337 (99.48%). It is worth mentioning that this species is the main vector of Leishmania infantum, showing the participation of Lutzomyia longipalpis in the transmission of Visceral Leishmaniasis in the studied municipalities. Studies on sandflies are essential to help in vector control and, consequently, in the control of leishmaniasis.